2008
DOI: 10.1002/ajh.21249
|View full text |Cite
|
Sign up to set email alerts
|

International MDS risk analysis workshop (IMRAW)/IPSS reanalyzed: Impact of cytopenias on clinical outcomes in myelodysplastic syndromes

Abstract: The International Prognostic Scoring System (IPSS) was created for evaluating clinical outcomes of patients with myelodysplastic syndromes (MDS). We evaluated the depth of cytopenias to determine whether this parameter could further refine the prognostic ability of the IPSS. Correlation was determined between the depth of cytopenias in 816 patients from the International MDS Risk Analysis Workshop database and patients' clinical features. Univariate analyses of hemoglobin (Hb), absolute neutrophil count, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
65
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 38 publications
0
65
0
Order By: Relevance
“…In addition, although not statistically significant in all risk groups, candidates for exclusion had lower mean blast percentages at MDS diagnosis. These factors positively correlate with improved prognosis and lower risk [37], and thus give biological support to the exclusion of these patients from the analysis (Table II).…”
Section: Discussionmentioning
confidence: 70%
“…In addition, although not statistically significant in all risk groups, candidates for exclusion had lower mean blast percentages at MDS diagnosis. These factors positively correlate with improved prognosis and lower risk [37], and thus give biological support to the exclusion of these patients from the analysis (Table II).…”
Section: Discussionmentioning
confidence: 70%
“…23,24 However, there are data indicating that platelet count levels alone lack additive prognostic information to the International Prognostic Scoring System (IPSS) regarding OS or time into AML evolution. 25 In AML, the impact of the platelet count on OS for adult patients up to 60 years of age harboring aberrations of chromosome band 11q23 has been published recently. In this study, a low platelet count (p50 Gpt/l) was found to negatively impact OS in the whole-patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the study of Kao et al [10] substantiates the observation that anemia is one the most important prognostic factors in myelodysplastic syndromes, and this observation should be used to guide clinical decision regarding therapeutic modalities and the timing of intervention.…”
mentioning
confidence: 68%
“…As Kao et al [10] underscore, the severity of anemia likely reflects inherently poorer marrow function. In addition, chronic anemia is known to be associated with increased mortality and morbidity per se in community-dwelling older adults and patients with chronic heart failure [11], primarily because lower hemoglobin is associated with greater functional impairment and worse exercise capacity [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation